2001
DOI: 10.1021/ja004315q
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Water in Carbohydrate−Protein Binding

Abstract: The interactions of trimannosides 1 and 2 with Con A were studied to reveal the effects of displacement of well-ordered water molecules on the thermodynamic parameters of protein-ligand complexation. Trisaccharide 2 is a derivative of 1, in which the hydroxyl at C-2 of the central mannose unit is replaced by a hydroxyethyl moiety. Upon binding, this moiety displaces a conserved water molecule present in the Con A binding site. Structural studies by NMR spectroscopy and MD simulations showed that the two compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
153
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(170 citation statements)
references
References 73 publications
11
153
2
Order By: Relevance
“…In the covalent complex, the relaxed conformation of the ring places the C-1 carboxylate group into the equatorial position, and this now hydrogen bonds to two of these waters. Several studies have indicated that water rearrangement plays an important role in carbohydrate-protein interactions (41,42). The ordering of five extra water molecules in the covalent complex would be expected to decrease the entropy, and subsequently increase the free energy of the system.…”
Section: Discussionmentioning
confidence: 99%
“…In the covalent complex, the relaxed conformation of the ring places the C-1 carboxylate group into the equatorial position, and this now hydrogen bonds to two of these waters. Several studies have indicated that water rearrangement plays an important role in carbohydrate-protein interactions (41,42). The ordering of five extra water molecules in the covalent complex would be expected to decrease the entropy, and subsequently increase the free energy of the system.…”
Section: Discussionmentioning
confidence: 99%
“…In 3HET, a hydroxyethyl group replaces the hydroxyl group at the C2 position of the central mannosyl residue. ITC data 24 showed a more favorable entropy contribution for the binding of 3HET to Con A, relative to 3MAN, which was initially interpreted as indicating the displacement of the conserved water. A subsequent crystallographic and computational study 25 showed that the water was not displaced, although its position was slightly distorted relative to that in the Con AÀ3MAN complex (Figure 1).…”
Section: à23mentioning
confidence: 97%
“…Despite the dismissal (on the grounds of correlated errors) of linear correlations between changes in ΔH°b ind and -TΔS°b ind that have been claimed empirically for protein-ligand association (and numerous other chemical processes), [19][20][21][22][23][24] it is clear that, often, changes in the structure of a ligand leads to large changes in enthalpy and entropy of binding, but that these changes compensate in a way that results in small changes in ΔG°b ind . [14,[25][26][27][28][29] There is, however, no unequivocal, molecular-level explanation for entropy-enthalpy compensation, and its origin-even at a conceptual level-remains a controversial subject, [30] despite the qualitative rationalizations for this phenomenon advanced by Dunitz, Williams, and others. [25,31,32] Although these suggestions "make intuitive sense," [32,33] at some level, there is so much in the hydrophobic effect that is nonintuitive (or perhaps intuitive at some level, but still very complicated), that we are currently suspicious of simple, intuitive rationalizations of the even more difficult subject of entropy-enthalpy compensation.…”
Section: Entropy-enthalpy Compensationmentioning
confidence: 99%
“…[14,[25][26][27][28][29] There is, however, no unequivocal, molecular-level explanation for entropy-enthalpy compensation, and its origin-even at a conceptual level-remains a controversial subject, [30] despite the qualitative rationalizations for this phenomenon advanced by Dunitz, Williams, and others. [25,31,32] Although these suggestions "make intuitive sense," [32,33] at some level, there is so much in the hydrophobic effect that is nonintuitive (or perhaps intuitive at some level, but still very complicated), that we are currently suspicious of simple, intuitive rationalizations of the even more difficult subject of entropy-enthalpy compensation.…”
Section: Entropy-enthalpy Compensationmentioning
confidence: 99%